PEMBERDAYAAN POSYANDU DESA CIKAKAK: MENCIPTAKAN LANSIA BERDAYA DENGAN MIND SET KEWIRAUSAHAAN SOSIAL DALAM MENINGKATKAN NILAI SLOW LIVING BANYUMAS - Titi Rahmawati; M. Musa Al Hasyim; Dimas Purbo Pambudi; Muhammad Riyan Fitria Ramdlani; Resya Nur Intan Putri; Shinta Julianti (LPPM STAI Muhammadiyah Probolinggo, 2025)
Community health cadres in Cikakak Village lack adequate knowledge about empowerment programs for the elderly to promote social entrepreneurship, with a predominant condition where young elderly individuals in Cikakak Village generally experience memory decline, occasional excessive worries, and a lack of self-confidence. There are 30 cadres who received training in Cikakak Village. The goal of empowering the elderly is to serve as a stimulus for them to develop a positive spirit and motivation regarding the importance of social entrepreneurship, thereby creating social value through collaboration among individuals, organizations, and communities as a form of social innovation. This allows for the establishment of a simple yet meaningful relaxed lifestyle mindset as a manifestation of a slow living lifestyle in Banyumas Regency. The methodology used is quantitative. This collaborative movement is carried out through several stages, including training, the establishment of discussion forum groups, and mentoring of posyandu cadres as facilitators. The results of the empowerment show an average increase in productivity of 69, sustainability of 82.5, equity of 79.5, and empowerment of 7.0 among the cadres in the context of social entrepreneurship thinking and efforts to implement a slow lifestyle in Banyumas. The existence of procedures and rules for the happy empowerment program is outlined in the cadre guidebook and has successfully established a pioneer discussion forum for the elderly in Cikakak village.